Pemanfaatan limbah kerang sebagai material kemasan primer lipstik berbasis desain berkelanjutan - Fernando, Ferry; Hutapea, Marchelia Indriyanti; Malik, Kendall (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
Conventional plastic-based cosmetic packaging constitutes a substantial contributor to environmental pollution. This investigation examines the application of gonggong shell (Strombus turturella) biocomposite as an alternative material for primary lipstick packaging systems. Five material formulations employing varied binding agents (water, chitosan, epoxy, and eco-resin) were systematically evaluated. An optimal eco-resin:shell ratio of 5:8 was determined, exhibiting superior mechanical properties and aesthetic characteristics. Material processing parameters included thermal treatment at 250°C, particle size refinement to 80 mesh (0.177 mm), and precision molding procedures. Packaging dimensions (85-95 mm × 12-14 mm) were determined through anthropometric analysis (50th-95th percentile) and incorporated a push-click-twist actuation mechanism. Bio-PLA material was integrated to augment structural integrity and aesthetic functionality. Three design alternatives were assessed utilizing parameters encompassing form effectiveness, innovation potential, ergonomic performance, and manufacturing feasibility. The final prototype demonstrates successful integration of sustainable material systems with functional performance requirements. This design framework advances environmentally responsible sustainable design principles. The research establishes the viability of shell biocomposite as a viable substitute for conventional petroleum-based plastics, contributing to sustainable transformation in the cosmetics industry.